STABILISATOR SISTEM TENAGA BERBASIS JARINGAN SYARAF TIRUAN BERULANG UNTUK SISTEM MESIN TUNGGAL - Widi Aribowo (Universitas Ahmad Dahlan, 2010)
In this paper, recurrent neural network (RNN) is used to design power system stabilizer (PSS) due to its advantage on the dependence not only on present input but also on past condition. A RNN-PSS is able to capture the dynamic response of a system without any delays caused by external feedback, primarily bythe internal feedback loop in recurrent neuron. In this paper, RNNPSS consists of a RNN-identifier and a RNN-controller. The RNN-Identifier functions as the tracker of dynamics characteristics of the plant, while the RNN-controller is used to damp the system’s low frequency oscillations. Simulation results using MATLAB demonstrate that the RNNPSS can successfully damp out oscillation and improve the performance of the system.